BEHAVIOUR OF MARINE MICROFLORA TOWARDS ANTIBIOTICS I. SENSITIVITY TOWARDS CHLORTETRA CYCLINE (CTC) - SURENDRAN, P K; IYER, K MAHADEVA (Fishery Technology, 2025)
The sensitivity of 61 cultures of bacteria isolated from!fish towards chlortetracycline (CTC) at 5 ppm and 20 ppm levelslhas been determined on two solid media, viz; sea water agar (SW A)and a distilled water based medium consisting of peptone, beefextract, glucose and NaCI (PBGA). The cultures employed consistedof (i) gram-negative rods of marine origin viz; Achromobacler,Pseudomonas, Vibrio and Flavobacterium and (ii) gram positive orgaÂ·nisms viz; Micrococci and Corynebacterium. Depending on theinhibition zone diameter, the order of CTC sensitivity was foundto be Pseudomonas < Vibrio < Achromoba.cter as determined onPBGA at CTC levels of 5 and 20 ppm. The SWA enhanced thedevelopment of resistance in majority of the cultures as comparedto PBGA. PBG broth containing CTC at less than 10 ppmexerted a bacteriostatic effect only while that containing 10 ppmor more exerted a bactericidal effect on Achromobacter, Pseudomonasand Micrococci cuhures. The significance of these results in fishpreservation by CTC is discussed.